Armed Conflict in Asia - EAA Editorial Office (Education About Asia, 2021)
Learning about the profound multiple causes and effects of armed conflicts on past, present, and possible future generations is a critical component of a liberal education and an imperative part of reflective democratic citizenship, including, and especially, electing executive and legislative leaders.
Keywords: China; Conflict Studies; East Asia; International Relations; Japan; Korea; Military; Northeast Asia; Philippines; Vietnam; World History